2011
DOI: 10.2147/cia.s23656
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive treatment of lumbar spinal stenosis with a novel interspinous spacer

Abstract: PurposeTo assess the safety and effectiveness of a novel, minimally invasive interspinous spacer in patients with moderate lumbar spinal stenosis (LSS).MethodsA total of 53 patients (mean age, 70 ± 11 years; 45% female) with intermittent neurogenic claudication secondary to moderate LSS, confirmed on imaging studies, were treated with the Superion® Interspinous Spacer (VertiFlex, Inc, San Clemente, CA) and returned for follow-up visits at 6 weeks, 1 year, and 2 years. Study endpoints included axial and extremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Using the SF-36 questionnaire instrument, these authors reported a percentage improvement of 41% over preoperative scores for the PCS. Also employing the SF-36, Shabat et al [ 17 ] found a PCS improvement of 40% in 53 IPD-treated patients with intermittent neurogenic claudication followed for 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Using the SF-36 questionnaire instrument, these authors reported a percentage improvement of 41% over preoperative scores for the PCS. Also employing the SF-36, Shabat et al [ 17 ] found a PCS improvement of 40% in 53 IPD-treated patients with intermittent neurogenic claudication followed for 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown improved ODI scores, ZCQ scores, and decreased VAS levels after implantation of the device [25]. Some studies have shown minor increases in ODI and VAS at 2-year time points after initial drop following surgery [19,26].…”
Section: Next-generation Technologiesmentioning
confidence: 99%
“…There is a general agreement on immediate decreased ODI or ZCQ with the use of IPDs. Some studies have demonstrated a "bounce back" effect after 1 or 2 years for both ODI [12,18,25] and ZCQ [33,37]. Although outcome in terms of ODI or ZCQ appear similar between last-and next-generation IPDs, the literature lacks sufficient randomized trials recruiting both types.…”
Section: Symptom Reliefmentioning
confidence: 99%
“…7). Unlike X-Stop, the Superion is delivered percutaneously as a single-piece through a cannula after dilators have opened the interspinous space [15,16]. The implant has superior and inferior cam lobes that rotate during deployment, so as to capture the superior and inferior spinous processes (Fig.…”
Section: Superionmentioning
confidence: 99%